Synthesis, Characterization and Antibacterial Studies of the Mixed Ligand Complexes of Pd(II) and Pt(II) Ions with Phthalic Acid and Heterocyclic Amines - Hossain, Md Belayet; Salam, Md Abdus; Rashed, Abdur; Yousuf, MA (Bangladesh Pharmaceutical Journal, 2015)
Mixed ligand complexes of Pd(II) and Pt(II) ions with phthalic acid and heterocyclic amines were synthesized and characterized. The general formula of the complexes is [MLL/]; where, M = Pd(II)(1-2), Pt(II)(3); L = phthalate, C8H4O4, L/ = pyridine, C5H5N(1); 2-aminopyridine, C5H6N2(2) and 4-picoline, C6H7N(3). The complexes were synthesized in the solid form and characterized by elemental analysis, electrical conductivity, magnetic measurements, and spectroscopic studies. Spectral analyses and magnetic measurements revealed the coordination of metal ion with ligands and geometry of the complexes. Anti-bacterial activity of the complexes against seven pathogenic bacteria (three gram positive and four gram negative) was assessed by the disc diffusion method. Complexes [Pd(Ph)(2-apy)] and [Pt(Ph)(4-pico)2] showed the highest anti-bacterial activity (when, Ph = bidentate phthalate, 2-apy = 2-aminopyridine and 4-pico = 4-picoline). DOI: http://dx.doi.org/10.3329/bpj.v17i2.22333 Bangladesh Pharmaceutical Journal 17(2): 157-162, 2014